Project for the analysis of land tenure and agricultural productivity in the Republic of Macedonia - Melmed-Sanjak, Jolyne; Bloch, Peter C.; Hanson, Robert (Land Tenure Center, University of Wisconsin-Madison, 1998)
The paper arises out of the Land Market Project and covers detailed data at the individual farm level and in-depth analyses of legal and historical processes. The agricultural sector in Macedonia is characterized by two very different farm enterprise types: small family farms operating on privately owned land, and large socially owned farms. About 30 percent of the total arable land in Macedonia belongs to socially owned farms. Most of the balance belong to the private farm sector; the cooperative sector occupies a small percentage of the arable land. The Land Markets Project addressed five tasks during the six-month term of the project: (1) assess the appropriateness of legislation, regulations, and institutions affecting land tenure and land use, (2) document and assess the land-related constraints to increased productivity and profitability of private farms, (3) document and assess the land-related constraints to increased productivity and profitability of socially owned farms, (4) propose land policy adjustments that would promote increased productivity and profitability of the agricultural sector, (5) identify financial and technical assistance to support the development of land markets that promote efficient, sustainable, and equitable increases in agricultural incomes. This paper reports the results of the first three tasks and then presents a comparative review of the land tenure and productivity results for both the private and the social sector. This comparison forms a basis for policy dialogue. The paper also includes a comprehensive discussion of the policy recommendations that stem from the Land Markets Project.
viii, 139 p.
Keywords: Land tenure Macedonia (Republic); Land use, Rural Economic aspects Macedonia (Republic); Farms, Size of Macedonia (Republic); Agriculture Economic aspects Macedonia (Republic); Agricultural productivity Macedonia (Republic); Land markets Macedonia (Republic); Agrarian structure Macedonia (Republic)